E-1: AN INVESTIGATIVE STUDY OF THE DISTORTION OF THE GEOGRAPHY OF THE HEBREW BIBLE TO CONCEAL THE PRESENCE OF ABRAHAM AND HIS DESCENDANTS IN THE ARABIAN PENINSULA - Akram, Noor (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
The Jewish people claim that the land promised to Ibrahim’s descendants was only for the children of Israel and that Hazrat Ibrahim and his descendants never came to the Arabian Peninsula. This claim is based on bragging, selfishness, and lies. The main characters of distortion are Levites and Jeroboam. The reasons for blaming them have been mentioned in this article in detail. Their claims neither logically nor historically meet the truth. The Torah admits that Hazrat Ismail was circumcised, and the Arabs used to circumcise, which was not practiced in any other nation except Arabs and Jews. Arabs also introduced themselves as descendants of Hazrat Ismail, and historically, they occupied Makkah and Zamzam as heirs. The Qur’an, on the other hand, does not mention the names of many regions or figures in many stories, possibly to prevent Ahle Kitab from spreading propaganda against the accuracy of the Holy Qur’an. The distortion in maps, names of cities, and races had allowed them to hide the reality. I have managed to solve the riddle of geographical changes by using archeological information of those areas. Reality shows that not only Ibrahim, Ismael, Isaac, and their early descendants but also Bani Israel themselves spent most period in Arabia.